Code Mixing on Person Talks in Catatan Najwa - Muhammad Saibani Wiyanto; Mevita Anisya Putri (Universitas PGRI Ronggolawe Tuban, 2023)
Everyone has their own style of language when interacting or communicating with other people. There are many variations of language styles, making people often use a mixture of two languages ​​in their communication. This in sociolinguistics is also known as Code Mixing. This incident also occurred in the YouTube video Catatan Najwa with Maudy Ayunda. The code mixing in this video is used to make it easier to convey messages to the audience. The aim of this study is to determine the kind of code-mixing using Hoffman's theory, namely intrasentential code-mixing, intralexical code mixing, and involving a change of pronunciation on the youtube video Catatan Najwa with Maudy Ayunda. A qualitative descriptive is employed in this study with content analysis as an approach. The results showed that speakers used the types of code-mixing according to the theory by Hoffman, intra-sentential code-mixing with 73% data, intra-lexical code-mixing with 22% data, and involving a change of pronunciation is 5% data.